The Female Version in Daphne Du Mauriers Rebecca - Ririn Pratiwi Suharto (Universitas Nahdlatul Ulama Blitar, 2020)
Rebecca is a novel which is created by Daphne Du Maurier. That novel is retold by Margaret Tarner in 1991. The main character of this novel is the narrator. This study uses A Freudian Psychological Analysis. The purpose of this study is to trace the Electra Complex (the female version of the Oedipus Complex) in Rebecca. So, the steps of this study are identify the symbolic father figure and the symbolic mother figure and trace how the main character tries to displace the symbolic mother figures in that novel. There are two results of this study. The first, Mr. De Winter is the symbolic figure father, while Mrs. Van Hooper, Rebecca, and Mrs. Danvers are the symbolic of mother figures. The second, the main character tries to displace the mother figures. The main character is marrying Mr. De Winter before Mrs. Van Hooper realizes her plan to make Mr. De Winter as the next victim. Then, the main character is trying to displace Rebecca by doing: (1) make social call with Beatrice and Giles, (2) prepare the best appearance for the Ball, and (3) cover her husband as murderer. Then, the main character is trying to displace Mrs. Danvers by convincing Mrs. Danvers to be her friend, but Mrs. Danvers decides to burn Manderley and go away from that place. Therefore, the narrator suffers Electra Complex and becomes the female version of the Oedipus Complex.